2017
DOI: 10.1016/j.applthermaleng.2016.08.099
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the inlet geometry on performance, surge margin and noise emission of an automotive turbocharger compressor

Abstract: Centrifugal compressor performance at low mass flow rates has become an issue in the latest years due to engine downsizing and the increase of low-end torque request. The principal drawback of this operating region is the appearance of the surge phenomenon, which is strongly affected by the compressor inlet geometry. This work is addressed to study the impact of different inlet geometries on the compressor performance, including compressor efficiency, noise emission and surge margin. An engine test bench is se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
40
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(45 citation statements)
references
References 31 publications
4
40
0
1
Order By: Relevance
“…The inflow is assumed to be inhomogeneous for both configurations; however, increased map width could be detected. Similar results were investigated by Galindo et al [5][6][7], Hou et al [8], Elkamel [9], Marelli et al [10] and Serrano [11]. In contrast to Kerres' results, Bayomi [12] stated that map width enhancement is gained by assembling flow straighteners upstream of the compressor, providing a more homogeneous inflow.…”
Section: Introductionsupporting
confidence: 75%
“…The inflow is assumed to be inhomogeneous for both configurations; however, increased map width could be detected. Similar results were investigated by Galindo et al [5][6][7], Hou et al [8], Elkamel [9], Marelli et al [10] and Serrano [11]. In contrast to Kerres' results, Bayomi [12] stated that map width enhancement is gained by assembling flow straighteners upstream of the compressor, providing a more homogeneous inflow.…”
Section: Introductionsupporting
confidence: 75%
“…Unfortunately, scarce data is available in the literature regarding the acoustic effect of turbocompressor inlet geometries. However, Karim et al [10] recently demonstrated that for instance inlet swirl vanes can achieve a reduction on the 4 -12 kHz noise band of the compressor, and Galindo et al [11] reported an overall noise influence of different nozzles, although no frequency content analysis was performed.…”
Section: Introductionmentioning
confidence: 99%
“…Phenomena leading to surge instabilities complicate the study of surge occurrence which may be associated to the compressor stall and may achieve a mild surge depending on the circuit acoustic resonance. For a high rotational speed of the compressor, the limit is difficult to characterize, and it is possible to switch abruptly to a deep surge [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Other methods as the analysis of the standard deviation of temperature signals [11] or frequency domain analysis [12,13] have also been applied on automotive turbocharger performances studies. Real-time quantification of the surge margin associated with an appropriate control would achieve the best performance of the system while maintaining stable operation, but it is still a challenge [3,4].…”
Section: Introductionmentioning
confidence: 99%